??????? ???????? ???????: ?????? ??? ????? ?????? ????????? ????????? ??? ????? - Zamani, Ahmad (Jurnal Ilmiah Ilmu Ushuluddin, 2012)
This paper discusses treatise concerning Muhammad preaching to the human rights andequality among humans. In this paper, the writer mentioned that Prophet Muhammadalways give attention to the issues of equality and human rights. He has tried in earnestto bring about equality of human rights. Among the steps he did, namely by sending amessage to the kings or rulers around Arab peninsule in that time. These messages cameto be known as Muhammad the sublime treatise, which became indication that Islam hadlong talks about equality and human rights. Everyone has equal rights and obligations.The differences between them over the contribution of the benifit works that can be given tomankind in general.